Metal-Protein Hybrid Materials: Unlocking New Frontiers in Biomedical Applications - Pan, Yong; Zhao, Han; Huang, Wenyong; Liu, Siyang; Qi, Yanxin; Huang, Yubin (Advanced healthcare materials, 2025)
Metal-protein hybrid materials represent a novel class of functional materials that exhibit exceptional physicochemical properties and tunable structures, rendering them remarkable applications in diverse fields, including materials engineering, biocatalysis, biosensing, and biomedicine. The design and development of multifunctional and biocompatible metal-protein hybrid materials have been the subject of extensive research and a key aspiration for practical applications in clinical settings. This review provides a comprehensive analysis of the design strategies, intrinsic properties, and biomedical applications of these hybrid materials, with a specific emphasis on their potential in cancer therapy, drug and vaccine delivery, antibacterial treatments, and tissue regeneration. Through rational design, stable metal-protein hybrid materials can be synthesized using straightforward methods, enabling them with therapeutic, delivery, immunomodulatory, and other desired functionalities. Finally, the review outlines the existing limitations and challenges associated with metal-protein hybrid materials and evaluates their potential for clinical translation, providing insights into their practical implementation within biomedical applications.